Structure and Properties of the Non‐Centrosymmetric Manganese(II) Borate Mn5(BO3)3OH. Issue 34 (2nd September 2019) - Falkowski, Viktoria; Zeugner, Alexander; Bayarjargal, Lkhamsuren; Saxer, Andreas; Ruck, Michael; Huppertz, Hubert
Abstract : The rose‐colored compound Mn5 (BO3 )3 OH was synthesized under high‐pressure/high‐temperature conditions of 2.5 GPa and 973 K in a Walker‐type multianvil press. Single‐crystal X‐ray structure determination yielded the non‐centrosymmetric monoclinic space group Pm (no. 6) with the lattice parameters a = 329.71(1), b = 1384.92(5), c = 902.37(3) pm, and β = 107.92(1)°. The presence of the hydroxide group is ascertained by vibrational spectroscopy. Magnetization experiments in the range from 300 to 14 K revealed paramagnetic behavior with antiferromagnetic ordering below 14 K and an effective magnetic moment of 12.2 µB per formula unit. The acentric nature of the material was verified by second harmonic generation measurements, yielding a considerably strong intensity (Isample /Iquartz = 11.14). Additionally, thermal investigations showed a several‐step transformation to Mn2 OBO3 upon heating under air. Abstract : High‐pressure synthesis of acentric Mn5 (BO3 )3 OH: By means of high‐pressure/high temperature synthesis, the non‐centrosymmetric manganese(II) compound Mn5 (BO3 )3 OH was obtained and characterized by single‐crystal and powder X‐ray diffraction. Additionally, vibrational spectroscopy, UV/Vis, thermoanalytical, magnetic, and SHG measurements were performed.